PENGARUH TEKNIK HIPNOTERAPI TERHADAP KARAKTERISTIK MUAL PADA PASIEN YANG MENJALANI KEMOTERAPI DI RUMAH SAKIT MITRA PLUMBON CIREBON - Ahmad Syaripudin (LPPM ITEKES Mahardika, 2018)
Background. Hypnotherapy is a hypnotic application in curing psychological disorders and relieving physical disorders. The mechanism of action of hypnosis is based on the subconscious. Some scientists speculate that hypnosis stimulates the brain to release neurotransmitters (chemicals in the brain), encephalin, and endorphins and suppress the hypothalamus, which functions to improve mood so that it can change the individual's acceptance of nausea. Purpose. This research aims to determine the effect of hypnotherapy techniques on the characteristics of nausea in patients who underwent chemotherapy in hospitals Mitra Plumbon Cirebon. Method. This study used pre experimental methods with non-randomized one group pre test and post test design performed on patients chemotherapy who experienced nausea. The sample in this study is the entire population of patients who have undergone chemotherapy and experienced nausea in the hospital Mitra Plumbon the total samples are 54 respondent data analysis used Wilcoxon Test. Result. The result of the research on 54 subjects in hypnotherapy showed the nausea characteristics of chemotherapy patients before and after hypnotherapy was 51 people with decreased nausea, 3 people with the result remained nauseous and nobody experienced increased nausea. Wilxocon Signed Ranks Test Test results obtained significancy value 0.000 (p, 0.05), thus there is a significant difference of nausea characteristics before after hypnotherapy. Conclusions. This suggests that hypnotherapy is effective and effective against the reduction of nausea characteristics in chemotherapy patients. It is hoped that the action of hypnotherapy can be made as an intervention in dealing with nausea.